Sompa and Dui Menre in Wedding Traditions of Bugis Society - Rusdaya Basri; Fikri Fikri (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This paper investigates the dynamics of sompa and dui’ menre’ in wedding traditions of Bugis society in Sidenreng Rappang Regency, South Sulawesi. Sompa in Bugis society is giving money or property to the wife that becomes the pillar and the legal requirement in the wedding traditions. Then, dui’ menre’ is the money from the groom that must be dedicated to the bride’s family as the budget for the wedding procession. The high value of sompa and dui’ menre’ in Bugis wedding tradition is determined by the social status of the bride and her parents that consists of nobility, wealth, higher education and her beauty. In terms of Maqasid al-Sharia perspective, dui’ menre’ has a mashlah}at ’ sides that can motivate the youths to work hard to have income and as the symbols of noble position for the woman. However, that tradition also leads some mudharat sides; for examples, many men failed to marry; there is a tendency for sirri marriage (unregistered marriage), they do eloping and they tend to delay the age of marriage (preferring to be celibacy or spinster).